Evaluation of the effects of dimethyl fumarate on transforming growth factor beta levels in the liver of rats with bile duct ligation-induced cholestasis - Hannaneh Vossoughi; Pejman Mortazavi; Mahsa Ale-Ebrahim; Razieh Hosseini (Toxicology Reports)
Background: Cholestasis is a reduction or cessation of bile flow in the biliary system, which can be life-threatening. Dimethyl Fumarate could induce anti-inflammatory and antioxidant effects in the body. Objective: This investigation focused on assessing the impact of Dimethyl Fumarate on liver levels of transforming growth factor beta (TGF-β) to mitigate biochemical, histopathological, and immunohistochemical alterations in cholestasis-induced rat models. Methods: Forty male adult Wistar rats were divided into eight groups (healthy control treated with distilled water, healthy rats treated with 50, 100, and 200 mg/kg of Dimethyl Fumarate, bile duct ligation (BDL), and experiment BDL groups were treated with 50, 100, and 200 mg/kg of Dimethyl Fumarate). After the gavage treatment period of 45 days, the rats were anesthetized and underwent blood sampling. Liver damage was assessed by measuring hepatic marker enzymes (alanine transaminase, aspartate transaminase, alkaline phosphatase, gamma-glutamyl transferase, and total bilirubin), histopathological (lesion assessment), and immunohistochemical (TGF-β expression level) observation. Results: The findings demonstrated that administration of varying doses of Dimethyl Fumarate via gavage led to a statistically significant reduction in serum concentrations of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, gamma-glutamyl transferase, and total bilirubin (P < 0.05). The optimal dosage identified was 200 mg/kg of Dimethyl Fumarate. Furthermore, the data indicated that gavage treatment with Dimethyl Fumarate significantly attenuated TGF-β expression level and mitigated hepatic damage (P < 0.05). Conclusion: This strategy may reduce inflammation, cholestasis, and fibrosis outcomes, attributed to its anti-inflammatory and antioxidant properties. Nonetheless, further research is necessary to substantiate these findings.